STIMULUS DAN KONSEKUENSI DARI CUSTOMER SATISFACTION: MODEL TERINTEGRASI PADA JASA KAFE - Budi Aryani; Sri Vandayuli Riorini (Jurnal Manajemen., 2014)
This research was based on the effects of Corporate brand image and Service quality on Customer loyalty through Customer satisfaction at 3 local cafes in Jakarta. The objectives of this research are: 1) to analyze the effect of Corporate brand image on Customer satisfaction, 2) to analyze of the effect of Customer satisfaction on Customer loyalty, 3) to analyze the direct effect of Corporate brand image on Customer loyalty, 4) to analyze of effect of Service quality on Customer satisfaction, 5) to know the direct effect of Service quality on Customer loyalty. This research involved 200 respondents within three specific criterias who have graduated minimum from junior high school, under 17 years old, and have visited 3 selected cafes for more than two times. Data analysis that was used for this research contains the complete sample of respondents, and purposive sampling method was applied. All the hyphotesis are analyzed by AMOS, prosessed by SPSS and tested by Structural Equation Model(SEM). The results of this research are: 1) Corporate brand image does not have any influence on Customer satisfaction and Customer loyalty at Jakarta local cafes, 2) Customer Satisfaction has a positive effect on Customer loyalty at Jakarta local cafes, 3) Service quality does not affect Customer satisfaction at Jakarta local cafes, and 4) Service quality is positively and significantly affecting Customer loyalty at Jakarta local cafes.